Infliximab versus intravenous immunoglobulin for refractory Kawasaki disease: a phase 3, randomized, open-label, active-controlled, parallel-group, multicenter trial - Masaaki Mori (Nature Portfolio, 2018)
Abstract We compared the efficacy and safety of infliximab with intravenous immunoglobulin (IVIG), a standard therapy, in a phase 3 trial (NCT01596335) for Japanese patients with Kawasaki disease (KD) showing persistent fever after initial IVIG. Patients with initial IVIG-refractory KD, aged 1–10 years, received a single dose of IV infliximab 5 mg/kg or IV polyethylene glycol-treated human immunoglobulin (VGIH) 2 g/kg on day 0. Primary outcome was defervescence rate within 48 h after the start of treatment. Safety was evaluated through day 56. Overall, 31 patients were randomized (infliximab, n = 16; VGIH, n = 15); 31.3% and 60.0% patients discontinued due to worsening KD. Defervescence rate within 48 h was greater with infliximab (76.7%) than VGIH (37.0%) (p = 0.023), and defervescence was achieved earlier with infliximab (p = 0.0072). Coronary artery lesions occurred in 1 (6.3%) and 3 (20.0%) patients receiving infliximab and VGIH, respectively, up to day 21. Adverse events occurred in 15 (93.8%) and 15 (100.0%) patients in the infliximab and VGIH groups, respectively. No serious adverse events in the infliximab group and one in the VGIH group were observed. Infliximab improved the defervescence rate within 48 h and time to defervescence versus standard therapy, and was well tolerated in patients with IVIG-refractory KD.